Construction and evaluation of China older-adult care service smart supply chain system - Dai, You-Yu; Liu, Guanlong; Sun, Long (Frontiers in Public Health, 2023)
As the aging of the population continues to deepen, the pressure on social pensions is gradually increasing, and the issue of assistance has become a problem that must be solved.With the development of science and technology, people's living standard is constantly improving. The elderly care services expected by the elderly are not limited to meeting the basic daily needs of individuals. The current industry should also consider how to combine modern science and technology with the elderly care service industry to better serve the elderly and enable elderly care service providers to move towards the service needs that make people happier and healthier. This research is about constructing and evaluating the smart supply chain of Chinese old-age services. Based on the research results of previous scholars, this paper divides the construction of the smart supply chain of China endowment service into four aspects: policy aspect, economic aspect, social aspect, and technical aspect; the four significant elements are divided into the first-level indicators, and 16 second-level indicators are divided under the first-level hands. The importance and satisfaction of each evaluation index were obtained by distributing questionnaires to the managers who study the supply chain and the employees who are related to the old-age service. After the reliability analysis, the importance-performance analysis (IPA) quadrant analysis chart of the evaluation index was constructed using importance-performance analysis. The index of creating an smart supply chain system for China's old-age service is given priority, the supply chain system of China's old-age assistance is further improved, and the social security of China's old-age service is enlarged.